Financial Crime Early Prevention Strategy: The Utilization of Whistleblowing System and Risk Management In Sharia Bank - Idrawahyuni; Sri Andayangsih; Andi Arifwangsa Adiningrat; Muhammad Adil; Endang Winarsih (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
This study examined the effects of using a whistleblowing system and risk management as prevention strategies for financial crimes at PT Bank Syariah Indonesia in South Sulawesi, Indonesia. This type of research used an associative quantitative approach with a population of 46 PT Bank Syariah Indonesia in South Sulawesi, Indonesia. The sample in this study comprised 230 respondents, selected using purposive sampling. The data were analyzed using multiple linear regression in SPSS 26. The results showed that the whistleblowing system cannot yet be used as an early prevention strategy for financial crime. In comparison, risk management has a positive and significant effect on the early prevention of financial crimes. It is hoped that the results of this research will make additional contributions to the literature on early prevention strategies for economic crimes in Sharia banking, focusing on whistleblowing systems and risk management. In addition, practitioners can provide input to management at PT Bank Syariah Indonesia in South Sulawesi on improving fraud prevention by increasing the effectiveness of the whistleblowing system and strengthening risk management as a prevention strategy against fraud.